Geology of the Eastern Part of the Volcanic-Kendeng Zone of East Java: Stratigraphy, Structures and Sedimentation Review from Besuki and Situbondo Areas - Agus Handoyo Harsolumakso; Dardji Noeradi; Alfend Rudyawan; Dadan Amiarsa; Satryo Wicaksono; Affan A Nurfarhan (Pusat Survei Geologi, 2019)
The Tertiary stratigraphy of Situbondo was constructed by a series of volcanoclastic-carbonate turbidite facies of Menuran Formation with Pacalan limestone Member, and Leprak Formation. These formations formed a regional east-west trending circular anticlinorium. The Tertiary formations were covered by Quaternary volcano-clastic Ringgit Formation and subsequent younger Bagor volcanic products. The oldest Tertiary rock units are the Late Miocene-Pliocene Menuran Formation, with Pacalan Limestone Member. Formation is mainly composed of foram-rich marls and calcareous, sometimes tuffaceous sandstones, with conglomerate intercalations. Sedimentation of this formation is interpreted as to be a mixing, from proximal to distal turbidite, involving volcaniclastic and carbonate sources, inÂ a bathyal open marine environment. The Early Pliocene Leprak Formation overlies conformably the Menuran Formation, which consists of alternating calcareous sandstones and tuff sandstones deposited in a bathyal open marine environment with proximal turbidite mechanism suggesting that basin depocenter was located to the east. Up to Late Pliocene, the region was dominated by developments proximal turbidite volcanoclastic sedimentation of The Leprak Formation, contemporaneous with increasing volcanic activity in the south. Deformation of Plio-Pleistocene in Java is believed to be the last major tectonic period, which forms the west-east trending structures. In Situbondo area, folding structures in this direction involves the Neogene Menuran Formation, Pacalan Member and Leprak Formation. Volcanic activity persists, and increases, with the activity of Ringgit-Beser volcano in Pleistocene. These late events of magmatism, volcanism and uplift were contributed to the last structural configuration of the area.Keyword : Situbondo, structural geology, volcanic-kendeng zone, stratigraphy